2020
DOI: 10.3389/fpsyg.2020.02143
|View full text |Cite
|
Sign up to set email alerts
|

(Not so) Great Expectations: Listening to Foreign-Accented Speech Reduces the Brain’s Anticipatory Processes

Abstract: This study examines the effect of foreign-accented speech on the predictive ability of our brain. Listeners actively anticipate upcoming linguistic information in the speech signal so as to facilitate and reduce processing load. However, it is unclear whether or not listeners also do this when they are exposed to speech from non-native speakers. In the present study, we exposed native Dutch listeners to sentences produced d non-native speakers while measuring their brain activity using electroencephalography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Obleser and Kotz (2011) experimentally manipulated stimulus degradation via noise vocoding (see Shannon et al, 1995) and found that the N400 mean amplitude decreased and peak latency increased as speech intelligibility decreased (see also Strauβ, Kotz, & Obleser, 2013;Aydelott et al, 2006). Similarly, Romero-Rivas and colleagues (2016) reported findings in which there was a reduced N400 context effect when listening to foreign-accented speech, which is also theorized to induce listening effort (see also Goslin et al, 2012;Schiller et al, 2020). Collectively, these studies suggest that a listener's ability to use context to facilitate online lexical semantic processing may be compromised when listening to perceptually challenging speech.…”
Section: Electrophysiological Studies Of Context Use and Listening Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…Obleser and Kotz (2011) experimentally manipulated stimulus degradation via noise vocoding (see Shannon et al, 1995) and found that the N400 mean amplitude decreased and peak latency increased as speech intelligibility decreased (see also Strauβ, Kotz, & Obleser, 2013;Aydelott et al, 2006). Similarly, Romero-Rivas and colleagues (2016) reported findings in which there was a reduced N400 context effect when listening to foreign-accented speech, which is also theorized to induce listening effort (see also Goslin et al, 2012;Schiller et al, 2020). Collectively, these studies suggest that a listener's ability to use context to facilitate online lexical semantic processing may be compromised when listening to perceptually challenging speech.…”
Section: Electrophysiological Studies Of Context Use and Listening Effortmentioning
confidence: 99%
“…Although research on listening effort dates back to the 1960s (e.g., Rabbitt, 1968), the factors underlying effortful listening and its impacts on higher level language comprehension are not well understood. For example, although it has been proposed that listeners can use semantic and syntactic information available in the ongoing linguistic context to mitigate the effects of effortful listening (e.g., Pichora-Fuller, 2008;Sheldon et al, 2008;Benichov et al, 2012;Lash et al, 2013), other work in a growing body of research in the field of cognitive electrophysiology that has shown that a listener's ability to use context to facilitate online word processing (e.g., as reflected by the N400 component of the event-related brain potential, ERP), is reduced when listening is more effortful (e.g., Romero-Rivas et al, 2016;Schiller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of early brain activity, suggesting that there was no word anticipation, was indicated by the absence of phonological mismatch negativity (PMN) in foreign-accented speech. By contrast, later ERP components did not reveal any significant difference between native and foreign-accented speech processing, implying that listeners’ overall performance was not affected depending on whether they listened to sentences in native or non-native accents (Schiller et al, 2020 ). This shows that foreign-accented speech only affected the early stages of speech processing and there was no difference in the understanding of native and foreign-accented speech at a later stage.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, it was noted that the level of semantic activation appeared more superficial when listeners heard the sentences in a foreign accent, implying a differential processing of native-accented and foreign-accented speech. To address this point and investigate the aspect of anticipation directly, a recent ERP study was conducted that aimed to provide more insight into whether foreigner-accented speech reduces or increases anticipation (Schiller et al, 2020 ). It used a within-participants design and monitored brain-activity before the presentation of the critical word.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation